THE EFFECT OF THE SATISFACTION OF ACTIVITIES PRIOR AND AFTER TRAVEL EPISODES, AND THE INVOLVEMENT OF PEOPLE ON TRAVEL SATISFACTION - WONG, ADRIAN GUO NENG (Universiti Teknologi PETRONAS, 2021)
Travelling is a necessity for people in general to fulfil their needs, desires, or to participate in an activity that must be conducted in a specific location. Whenever an individual travels, there is an expectation that is set upon the traveller on the trip in which he or she wishes to fulfil. This can be defined as travel satisfaction and measures the overall level of fulfilment with the traveller’s expectation. Utilizing the 2017 Bandung Metropolitan Area (BMA) dataset, this study aims to expand the research on travel satisfaction in the context of time-space approach in greater detail through the usage of bivariate analysis. This paper will investigate the bivariate analysis of socioeconomic factors, travel parameters and geographical factors to travel satisfaction, as well as determining the bivariate analysis of the effect of the satisfaction of activities conduction prior and after the travel episode, and the effect of the involvement of other person on an individual’s travel satisfaction